Operative delivery combined with splenectomy- a case series - Fernando, M.M.P.; Wijeyaratne, C.N.; Tudawe, M.; Liyanage, P.; Kaluarachchi, A; Randeniya, C.; Wijeyaratne, S.M.; Sheriffdeen, A.H. (Sri Lanka College of Obstetricians and Gynecologist, 2005)
BACKGROUND: Immune thrombocytopenic purpura (ITP) can complicate pregnancy, which requires optimal inter-disciplinary management to prevent maternal and perinatal complications. Current recommendations are for vaginal delivery unless obstetrically indicated. We report a case series of medically and obstetrically complicated ITP referrals from multiple geographic locations in Sri Lanka, where the best option was a combined splenectomy and operative delivery. RESULTS: Between January 2003 to June 2005, 5 pregnant women with thrombocytopaenia were referred to a single tertiary care unit. Age range: 28 - 35 years; POA ranging from 29 40 weeks. Three were primigravidae. One was in her 5th pregnancy with no living children and another in her 8th pregnancy with 2 living children. The latter two had severe PIH previously with fetal loss; the P5 complicated by ileofemoral DVT and the P8 diagnosed to have antiphospholipid syndrome and SLE. Platelet counts ranged from 2,000- 40,000/?l despite all receiving steroid pulses and immunosuppression and 3 also receiving additional intravenous immunoglobulin. The P8C2 had an intrauterine death at 29 weeks, whilst the others had a viable fetus. All were managed by a team of obstetric and medical specialists, who reached a consensus decision to deliver four by Caesarean, combined with splenectomy; and the IUD by abdominal hysterectomy combined with splenectomy under general anaesthesia. Surgery was tolerated well with no excessive haemorrhage and maternal platelet counts recovered within 12 hours of splenectomy. Neonatal outcome was good in 4/4 with one developing transient thrombocytopaenia. DISCUSSION AND CONCLUSION: Optimum individualized medical and surgical management of severe maternal immune thrombocytopaenia in pregnancy with a multidisciplinary approach in a tertiary centre is recommended in the Sri Lankan setting.
Keywords: SPLENECTOMY